Chondroid syringoma of the forearm: A case report of a rare localization - Koroush Askari; Ghazaleh Ghorbani; Navid Yousefi; Seyed Saadat; Seyedeh Nazanin Seyed Saadat; Omid Zargari (Wolters Kluwer Medknow Publications, 2014)
Chondroid syringoma (CS) is an uncommon benign adnexal tumor of the skin with eccrine and apocrine origin, which usually involves the head and neck region. The presentation of CS in other areas of the body is rare. A 45-year-old male patient presented to the dermatology clinic with a chief complaint of a painless, slow-growing mass on his left forearm, which gradually developed over the course of 2 years. A solitary, firm, purple, mobile, non-tender nodule was located in the distal part of left dorsal forearm, which was 1.8 cm in diameter. The tumor was surgically excised and sent for the histopathological evaluation. Results of biopsy and hematoxylin and eosin staining confirmed the diagnosis of CS and showed no evidence of malignancy. Although CS is an uncommon tumor in uppr limb region, it should be considered as one of the differential diagnoses, when dealing with tumors of this area.